Asia on tour [electronic resource] : exploring the rise of Asian tourism - Chang, T. C.; Teo, Peggy; Winter,Tim , 1971- (Routledge, 2009)
Examining domestic and intra-regional tourism, the book reveals how improvements in infrastructures, ever increasing disposable incomes, liberalized economies, the inter-connectivities of globalization and the lowering of borders, both physical and political, are now enabling millions of Asians to travel as tourists.